LEGAL PROTECTION OF POLICY HOLDERS AGAINST INSURANCE COMPANIES EXPERIENCED BANKRUPTCY - Mahatma, Laode Man (JILPR Journal Indonesia Law and Policy Review, 2024)
The unequal position between insurance policy holders and insurance companies as applied to standard agreements, causes the function of legal protection for insurance policy holders to be questioned. One of the institutions that has the authority and functions to provide legal protection is the Financial Services Authority (OJK) as regulated in Law Number 21 of 2011 Article 55 paragraph (1). The transfer of risk in an insurance agreement is carried out in return for a premium payment by the insured which is deemed commensurate with the risk that must be insured, although the claim payment as fulfillment of performance is not necessarily equal to the premium amount. The formulation of the problem discussed is: What are the effects of Insurance Company Bankruptcy Law on Insurance Engagements? What are the responsibilities of an insurance company experiencing bankruptcy towards policy holders to obtain their rights in accordance with the agreement? What are the legal remedies for policyholders in the bankruptcy process? The research method used is a normative juridical method, namely analyzing legal issues, facts and other legal phenomena related to the legal approach, then obtaining a comprehensive picture of the problem to be studied. Based on the research results, the author concludes that the legal consequences of the bankruptcy of an Insurance Company give the Policy Holder the right to receive priority in receiving their rights to the distribution of their assets over other parties, and the responsibility of the company in the insurance sector which has been declared bankrupt to the holder's claim. policy from the insurance sector in the bankruptcy process, the directors have responsibilities during the bankruptcy process, from before until after the Company is declared bankrupt.